Assessment of Intramedullary Spinal Pressure in Small Breed Dogs With Thoracolumbar Disk Extrusion Undergoing Hemilaminectomy. Issue 8 (10th September 2015) - Noussitou, Fiammetta L.; Gorgas, Daniela; Rohrbach, Helene; Henke, Diana; Howard, Judith; Forterre, Franck
Abstract : Objective: To assess intramedullary spinal pressure (IMP) in small breed dogs with thoracolumbar disk extrusion. Study Design: Prospective cohort study. Animals: Small breed dogs (n = 14) with thoracolumbar disk extrusion undergoing hemilaminectomy and healthy chondrodystrophic laboratory dogs (control; n = 3) without spinal disease. Methods: Diagnosis was based on clinical and neurological examinations and magnetic resonance imaging (MRI) and was confirmed intraoperatively. A standardized anesthesia protocol and surgical procedure were used to minimize factors that could influence IMP. Intramedullary pressure was measured through a minidurotomy at the site of spinal cord compression using a fiber optic catheter inserted perpendicular to the longitudinal axis of the spinal cord. Measurements were taken after hemilaminectomy and again after removal of extruded disk material. Results: Affected dogs had significantly higher IMP compared to control dogs ( P  = .008) and IMP decreased significantly post‐decompression compared with initial values ( P  < .001). No correlation was found between IMP and neurologic grade, degree of spinal cord compression on MRI, or signal intensity changes on MRI. Conclusion: Acute thoracolumbar disk extrusion is associated with increased IMP in small breed dogs and surgical decompression results in an immediate decrease of IMP.